2009
DOI: 10.1007/s10103-009-0695-y
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength effect in temporomandibular joint pain: a clinical experience

Abstract: Temporomandibular disorders (TMDs) are common painful multifactorial conditions affecting the temporomandibular joint (TMJ) and whose treatment depends on the type and symptoms. Initially, it requires pain control, and, for this, drugs, biting plates, occlusal adjustment, physiotherapy or their association are used. Lately, laser phototherapy (LPT) has been used in the treatment of pain of several origins, including TMDs. This study reports the treatment of a selected group of 74 patients treated at the Laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
24

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 18 publications
0
64
0
24
Order By: Relevance
“…In all 3 groups, greater VAS reduction was observed after the application of 810 nm laser compared to 660 nm laser. In a study by Carvalho et al, it was observed that greater laser wavelength was associated with greater pain reduction 36 . Previous research showed that the effectiveness of LLLT is greater when used in the spectrum of 780 to 904 nm because of increased penetration.…”
Section: Discussionmentioning
confidence: 96%
“…In all 3 groups, greater VAS reduction was observed after the application of 810 nm laser compared to 660 nm laser. In a study by Carvalho et al, it was observed that greater laser wavelength was associated with greater pain reduction 36 . Previous research showed that the effectiveness of LLLT is greater when used in the spectrum of 780 to 904 nm because of increased penetration.…”
Section: Discussionmentioning
confidence: 96%
“…TMR, orofasiyal bölgedeki odontojen kaynaklı olmayan ağrının başlıca sebebidir ve iskelet-kas rahatsızlıklarının bir alt sınıfı olarak değerlendirilir (1). TMR, başlıca semptomları kas ve eklem ağrıları, alt çene hareketleri ve ağız açıklığında kısıtlanma ve eklem sesleri olan multifaktöriyel durumlardır (2). Toplumun %40'ından fazlası bu belirtilerin en az birine sahiptir fakat bunların sadece dörtte biri bu belirtilerin farkındadır ve %10-20'si tedavi gereksinimi duymaktadır (3).…”
Section: Introductionunclassified
“…NSAİİ enflamasyonu önlemede başarılı olsa da gastroentestinal yakınmalar ve nefrotoksisite gibi komplikasyonların artışına sebep olabilmektedir (7). Bu noktada Düşük Seviyeli Lazer Terapisi (DSLT), kolay uygulanabilmesi, sınırlı tedavi süresi, analjezik, antienflamatuar, rejeneratif etkileri ve minimum yan etkiye sahip olması sebebiyle iskelet-kas rahatsızlıklarının tedavisinde alternatif bir tedavi seçeneği olarak karşımıza çıkmaktadır (2). (10).…”
Section: Introductionunclassified
“…For laser therapy applications, it is important to know the penetration and heat generation of laser in tissue in order to select optimal criteria such as wavelength, fluence, and beam size to afford the desired penetration for stimulating tissue healing in deep seated pathologies [23,24]. LLLT has demonstrated a number of biological and clinical efficacious results for muscle treatment, but this therapy has not been fully supported by scientific evidence due to the absence of quantitative assessments and treatment feedback data in real time.…”
Section: Introductionmentioning
confidence: 99%